2016
DOI: 10.12928/telkomnika.v14i4.3230
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Analysis of Reversible logic Based Arithmetic Logic Unit

Abstract: There is a tremendous growth in fabrication from small scale integration (SSI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…The mix of the output signal, in any case, can give the specific status of the input mix. This is the fundamental motivation to name these (n, n) gates reversible logic gates [23][24][25]. Fig.…”
Section: Reversible Logic Gatementioning
confidence: 99%
“…The mix of the output signal, in any case, can give the specific status of the input mix. This is the fundamental motivation to name these (n, n) gates reversible logic gates [23][24][25]. Fig.…”
Section: Reversible Logic Gatementioning
confidence: 99%
“…The comparative analysis and implementation of all significant research contributions in existing architectures is reported [17]. In research work [18], authors proposed two approaches of ALU design.…”
Section: Introductionmentioning
confidence: 99%
“…Honesty, which is free from plagiarism in the publication of scientific works. In general, the line quotation is indicated by the number of times the article has been quoted by other article means, the article cited is said to have good quality [6]. The scientific code of ethics statement is a code of ethics statement for all parties involved in the process of publishing scientific journals, namely managers, editors, bestari partners and writers.…”
Section: Introductionmentioning
confidence: 99%